Os rumos do conceito de mito e a fenomenologia peirciana - Sancassani, Victor (2018)
There are innumerable conceptions of myth throughout the history of human knowledge. However, it is possible to divide the theoretical studies of myth into two poles of the same axis, which keep them intrinsically connected: a current that began apparently in Ancient Greece and another that is nowadays, derived from the development of Modern Sciences in the nineteenth century. Yet, there is no specific scientific branch of study of myths, being dissolved in many fields of knowledge – anthropology, sociology, psychology, literature, philology, history, philosophy, religious studies etc., fragmentation that is also seen in the attempts to classify the phenomenon, but which comes from its very nature. Myth not only appears as a form of communication – narrative, oral, written, ritualistic, sacred, ideological etc. – but also is connected with human forms of communication. The preoccupations of myth extend from the metaphysical, cosmological, social, even to the individual and psychological level, due to its scope and ancestry, which makes possible to consider it as a forerunner of the forms of knowledge that we have today, as of thought itself, or else as acting in the present. It is in this sense that our work has a double objective. Firstly, due to a lack of studies and works that cover theories of myth in Portuguese and, mainly, in Brazil, we intend to explore and provide some of the main contributions that have highlighted the study of myths, which refer to the extremes of mythic theories, filling this epistemic gap that prevents students from taking knowledge of mythological theories or using them appropriately and not only peremptorily. On the other facet of our objective, we also want to corroborate with an initial contribution to the sciences of myth – which seem to have been restricted to the field of classifications and specificities in sociocultural manifestations – by introducing the Phenomenology of Charles Sanders Peirce as the architectural foundation to investigate and to evidence the omnipresence and interrelation of the universal categories of experience present in the myth, in its aspects of positive and creative spontaneity (Firstness), of reaction and existence (Secundity) and of regularity and infinite continuity (Thirdness)